1987
DOI: 10.1149/1.2100648
|View full text |Cite
|
Sign up to set email alerts
|

Uniformly Thick Selective Epitaxial Silicon

Abstract: The growth rate of selective epitaxial silicon is a function of the nucleation site seed area and the ratio of the area of the SiO2 mask to silicon area exposed. Therefore, with commonly employed IC circuit patterns, it is difficult to achieve, using conventional epitaxial growth conditions, silicon deposit thickness uniformity needed for IC processing. This constitutes one of the main obstacles to utilizing CVD selective epitaxy as an SOI process or as a replacement of LOCOS for oxide isolation. Reported in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…It should also be noted that without the presence of the AIC poly-Si layer, silicon nanowires do not grow on the fused quartz during the typical growth period (2-3 mins). The lack of Si nanowire nucleation on bare fused quartz is believed to arise from the selective nature of silicon thin film deposition using SiCl 4 , where the HCl produced from the reaction of SiCl 4 and H 2 suppresses the nucleation of silicon on an SiO 2 surface [14]. In the case of silicon nanowire growth by VLS, gold particles are present on the fused quartz surface, however, without the AIC Si layer, there is insufficient silicon present on the surface to form a supersaturated Au-Si alloy droplet which is needed for nucleation and growth of a silicon nanowire with SiCl 4 .…”
Section: Resultsmentioning
confidence: 99%
“…It should also be noted that without the presence of the AIC poly-Si layer, silicon nanowires do not grow on the fused quartz during the typical growth period (2-3 mins). The lack of Si nanowire nucleation on bare fused quartz is believed to arise from the selective nature of silicon thin film deposition using SiCl 4 , where the HCl produced from the reaction of SiCl 4 and H 2 suppresses the nucleation of silicon on an SiO 2 surface [14]. In the case of silicon nanowire growth by VLS, gold particles are present on the fused quartz surface, however, without the AIC Si layer, there is insufficient silicon present on the surface to form a supersaturated Au-Si alloy droplet which is needed for nucleation and growth of a silicon nanowire with SiCl 4 .…”
Section: Resultsmentioning
confidence: 99%
“…12 However, for this process it has also been shown that some control of loading effects and pattern dependency can be achieved by adjusting the partial pressure of HCl. 13,14 A CVD deposition on blanket wafers may be described using the classical boundary layer theory. 15 In this theory, a laminar gas stream is flowing over the wafer.…”
Section: Resultsmentioning
confidence: 99%
“…These results demonstrate the general trend that the deposition rate will increase as the area covered by oxide increases either globally and in the direct vicinity of an opening to Si. These trends are related to the selective nature of the deposition and are also wellknown from selective silicon epitaxy (12,13). CVD deposition on blanket wafers may be described using the classical boundary layer theory (14).…”
Section: Effect Of Oxide Coverage and Window Sizementioning
confidence: 99%